Thinking from the Qur’ānic perspective - Ishak, Mohd. Shuhaimi; Wan Yusoff, Wan Mazwati (ISTAC, 2015)
The Qur’ān is the main reference and source of knowledge for Muslims. It logically follows that understanding the concept of thinking should also be referred to the Qur’ān. Even though the word ‘intellect’ is mentioned 49 times in the Qur’ān, and there are hundreds of verses that urge Muslims to think, the theory of thinking from the Qur’ānic perspective has not been extensively explored to guide Muslim educators, curriculum designers and developers. Hence, this paper attempts to explore the concept of good thinking from the Qur’ānic perspective. It extensively examines verses of the Qur’ān pertaining to the intellect and thinking to come up with a theory of good thinking. From the analysis of the relevant Qur’ānic verses, the research found that the intellect is capable of rational and spiritual cognition as a result of applying critical, creative, ethical and spiritual thinking. Therefore, the research posits that good thinking from the Qur’ānic perspective is multi-dimensional; the dimensions are critical, creative, ethical and spiritual thinking. Furthermore, according to the Qur’ān, the aim of good thinking is to achieve wisdom. Hence, this paper also explicates the meaning of wisdom from the Qurānic perspective.